OPTIMIZING CAPITAL STRUCTURE TO IMPROVE CORPORATE FINANCIAL PERFORMANCE - Ahmad Muhammad Saribi; Adhista Setyarini; Sri Dewi Yusuf (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The purpose of this study is to investigate how optimizing the capital structure can enhance a company's financial performance. This study gathers and examines information from numerous pertinent theoretical and empirical sources using the literature research approach in order to gain a thorough grasp of the connection between capital structure and corporate financial performance. The findings indicate a positive relationship between the financial success of the business and capital structure optimization. The implementation of the optimal proportion of debt and equity is proven to be able to reduce the cost of capital, while optimizing the rate of return on investment (ROI) and return on equity (ROE). However, research also indicates that the suitability of capital structure is highly dependent on industry context, firm characteristics, and market conditions. Thus, companies need to adjust their capital structure strategy by considering these factors to achieve optimal financial performance improvement.